If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 27 = 9x + -7 Reorder the terms: 27 + 7x = 9x + -7 Reorder the terms: 27 + 7x = -7 + 9x Solving 27 + 7x = -7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 27 + 7x + -9x = -7 + 9x + -9x Combine like terms: 7x + -9x = -2x 27 + -2x = -7 + 9x + -9x Combine like terms: 9x + -9x = 0 27 + -2x = -7 + 0 27 + -2x = -7 Add '-27' to each side of the equation. 27 + -27 + -2x = -7 + -27 Combine like terms: 27 + -27 = 0 0 + -2x = -7 + -27 -2x = -7 + -27 Combine like terms: -7 + -27 = -34 -2x = -34 Divide each side by '-2'. x = 17 Simplifying x = 17
| 4(x+2)-10=2(x+3) | | K/9=99 | | 5+4p=6p-9 | | 8X=32/3 | | -2(6n-7n)+5n=145 | | 5(3s+8)=180 | | -4-6v=10-4r | | -3*a-6=24 | | X+27=x+77 | | a(2l+8)=80 | | -8r=-10r+10 | | Log5/7=1/3 | | -4/7•11 | | 3(5w+4)=12w-11 | | -8/15t=9/10 | | yx+-1=5x+3 | | 9*a+5+2=11 | | 3(x-6)+3x=24 | | -8=5-v | | -5h-9=6-8h | | 3s=-s-8 | | 3x-57=42 | | xy-1=5y+3 | | 28=5(w+6)-7w | | 126=6n^2+n-1 | | -5g+6=-7g | | -5c-8=-6c | | -15=-5v+8(v-3) | | 8x=3x+48 | | x^2-34x-44=-34x+37 | | 5(5-n)=75 | | -9-b=2b |